Countering Constitutional Crises within the African Union Framework: Legality, Legitimacy and Suitability - Kwaku Agyeman-Budu (Recht in Afrika, 2022)
The African Union (AU), which succeeded the Organisation of African Unity (OAU) in 2002, is based on a strong legal and institutional framework that reinforces constitutionalism at national, regional and continental levels. This framework is a response to the failure of the OAU to tame autocratic tendencies within its member states. It cements the organisation’s commitment to infuse the ideals, values and norms of constitutionalism into the conduct of domestic affairs and politics. The relevance of the framework stems from its ability, when adhered to by all member states, to prevent constitutional crises, many of which have a negative impact on national, regional and continental peace and security and often hinder the prospect of constitutional democracy. Using examples of AU interventions to stymie constitutional crises in the form of unconstitutional changes of government in the Central African Republic, Burundi and Southern Sudan, this paper highlights the dialectical relationship between constitutionalism, peace and security, which can ensure that AU interventions reinforce, rather than undermine, constitutional ideals. While noting the AU’s inability or unwillingness to apply this framework in all the constitutional crises it has been called upon to address, the article concludes that member states and the AU itself need to commit to the ideals of constitutionalism, otherwise the transformative constitutional framework will remain a mere paper tiger.